Grazing by the calanoid copepod Neocalanus cristatus on the microbial foodweb in the coastal Gulf of Alaska - Liu, Hongbin; Dagg, Michael J.; Strom, Suzanne (Journal of Plankton Research, 2005)
Neocalanus cristatus feeding on phytoplankton and microzooplankton was measured in the coastal Gulf of Alaska during spring and early summer of 2001 and 2003. N. cristatus CV fed primarily on particles > 20 µm. Particles in the 5 - 20 µm size range were ingested in some experiments under non-bloom conditions but not under bloom conditions. Particles < 5 µm were not ingested but increased during incubations because N. cristatus consumed their microzooplanktonic predators. N. cristatus are sufficiently abundant in nature to induce such a cascade effect in situ . Microzooplankton provided more than 70% of the carbon ingested by N. cristatus under non-bloom conditions but only about 30% under bloom conditions. N. cristatus ingested about 2 times more carbon under bloom conditions (average 21.4 µg C cop-1 d-1) than under non-bloom conditions (average 10.0 µg C cop-1 d-1) but these rates were inadequate to meet nutritional demands for growth and metabolism, estimated to be between 40 and 140 µg C cop-1 d-1. We believe our ingestion rates are underestimates of in situ rates because (1) we are underestimating consumption rates of large particles, (2) we may not be including some very large particles that should be considered as diet items, and (3) we are not properly accounting for the ingestion of aggregates. The feeding behavior of N. cristatus , one of the most abundant copepods in the North Pacific Ocean, remains incompletely understood.